Bactericidal nanopatterns generated by block copolymer self-assembly. (August 2020) - Fontelo, R.; Soares da Costa, D.; Reis, R.L.; Novoa-Carballal, R.; Pashkuleva, I.
Abstract: We describe the bactericidal capacity of nanopatterned surfaces created by self-assembly of block copolymers. Distinct nanotopographies were generated by spin-coating with polystyrene- block -poly(2-vinylpyridine) (PS- b -P2VP) followed by solvent vapor annealing. We demonstrate that the bactericidal efficiency of the developed coatings depends on the morphology and the chemistry of the surface: cylindrical nanotopographies presenting both blocks at the surface have stronger bactericidal effect on Escherichia coli than micellar patterns with only PS exposed at the surface. The identified mechanism of bacterial death is a mechanical stress exerted by the nanostructures on the cell-wall. Moreover, the developed nanopatterns are not cytotoxic, which makes them an excellent option for coating of implantable materials and devices. The proposed approach represents an efficient tool in the fight against bacteria, which acts via compromising the bacterial wall integrity. Statement of Significance: Bacterial infections represent an important risk during biomaterial implantation in surgeries due to the increase of antibiotic resistance. Bactericidal surfaces are a promising solution to avoid the use of antibiotics, but most of those systems do not allow mammalian cell survival. Nanopatterned silicon surfaces have demonstrated to be simultaneously bactericidal and allow mammalian cell culture but are made by physical methods ( e.g. plasma etching) applicable to few materials and small surfaces. In this article we show that block copolymer self-assembly can be used to develop surfaces that kill bacteria ( E. coli ) but do not harm mammalian cells. Block copolymer self-assembly has the advantage of being applicable to many different types of substrates and large surface areas. Graphical abstract: Image, graphical abstract